Il cambiamento climatico e l’impatto sulla salute: le pathoclima - Buizza, Roberto; Misiti, Francesco; Sannella, Alessandra (SocietàMutamentoPolitica, 2023)
Climate change has been accelerating, and this has been causing an increase of the number of intensity of its impacts on communities, including on their health. This link between climate change and health, a theme that we have named “pathoclima” (a neologism of the authors), an amplification of pathologies due to the increasing impact of climate change on society and the environment, is the subject of this contribution. Firstly, we present an analysis of the state of the climate and its impact on some respiratory, neurodegenerative, and mental health diseases. Then, we discuss some of the main conclusions of the Intergovernmental Panel on Climate Change (IPCC) report, and finally, we suggest that only through a transdisciplinary approach can we achieve the goal of zero net emissions by 2050. Only following a transdisciplinary approach, we could address climate change taking into account also all biological and sociological aspects of the problem.